1987
DOI: 10.1093/oxfordjournals.eurheartj.a062374
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular thrombi after short-term high-dose anticoagulants in acute myocardial infarction

Abstract: To examine the effect of short-term, high-dose anticoagulation on the subsequent occurrence of left ventricular (LV) thrombi after a first anterior wall acute myocardial infarction (AMI), 21 patients received placebo and 21 high-dose anticoagulants during the first 10 days of the acute infarction. They were studied with cross-sectional echocardiography 10 days and 1.3 and 6 months post infarction. At 1 month, 6 of 7 thrombi present in the placebo group at 10 days were still visible. No thrombi were detected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…Regression in size of the thrombus was seen in those treated with anticoagulation. Low levels of symptomatic systemic embolization were seen in this and other studies that demonstrated similar incidence (Visser et al, 1985;Johannessen et al, 1987;Keren et al, 1990). In a review, Cregler (1992) advocated 3 months of warfarin therapy for those with large anterior myocardial infarction or post-infarct heart failure.…”
supporting
confidence: 84%
“…Regression in size of the thrombus was seen in those treated with anticoagulation. Low levels of symptomatic systemic embolization were seen in this and other studies that demonstrated similar incidence (Visser et al, 1985;Johannessen et al, 1987;Keren et al, 1990). In a review, Cregler (1992) advocated 3 months of warfarin therapy for those with large anterior myocardial infarction or post-infarct heart failure.…”
supporting
confidence: 84%
“…Regression in size of the thrombus was seen in those treated with anticoagulation. Low levels of symptomatic systemic embolization were seen in this and other studies that demonstrated similar incidence (Visser et al, 1985;Johannessen et al, 1987;Keren et al, 1990). In a review, Cregler (1992) advocated 3 months of warfarin therapy for those with large anterior myocardial infarction or post-infarct heart failure.…”
Section: Comment On Guidelines On Oral Anticoagulation With Warfarin4supporting
confidence: 65%
“…A recent, preoperative cerebrovascular accident presents another situation in which delaying the operation may reduce the perioperative neurological risk. Evidence of a hemorrhagic component to the cerebrovascular accident, based on the results of a computed tomography scan, identifies those patients at particular risk for extension of the neurological damage due to heparinization and CPB (189). It is generally believed that a delay of 4 weeks or more is prudent if coronary anatomy and symptoms permit.…”
Section: (Level Of Evidence: C)mentioning
confidence: 99%